2023
DOI: 10.4049/jimmunol.2300252
|View full text |Cite
|
Sign up to set email alerts
|

Complement Receptor C3aR1 Contributes to Paclitaxel-Induced Peripheral Neuropathic Pain in Mice and Rats

Jijun Xu,
Ping Huang,
Bihua Bie
et al.

Abstract: Cancer chemotherapy-induced neuropathic pain is a devastating pain syndrome without effective therapies. We previously reported that rats deficient in complement C3, the central component of complement activation cascade, showed a reduced degree of paclitaxel-induced mechanical allodynia (PIMA), suggesting that complement is integrally involved in the pathogenesis of this model. However, the underlying mechanism was unclear. Complement activation leads to the production of C3a, which mediates inflammation thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…On the other hand, a growing body of evidence highlights MLT’s potential to enhance the efficacy of chemotherapy while mitigating its adverse effects . Despite its effectiveness as a cancer treatment, chemotherapy is limited by the significant side effects and causes, particularly peripheral neuropathic pain, by inducing nociceptive neuronal sensitization in DRG neurons . Notably, recent investigations have indicated that MLT is a promising avenue for preventing the development of painful neuropathy induced by chemotherapy. , Nonetheless, the intricate mechanisms underlying MLT/MT2’s protective role in DRG neurons in chemotherapy-induced neuropathic pain require further elucidation.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a growing body of evidence highlights MLT’s potential to enhance the efficacy of chemotherapy while mitigating its adverse effects . Despite its effectiveness as a cancer treatment, chemotherapy is limited by the significant side effects and causes, particularly peripheral neuropathic pain, by inducing nociceptive neuronal sensitization in DRG neurons . Notably, recent investigations have indicated that MLT is a promising avenue for preventing the development of painful neuropathy induced by chemotherapy. , Nonetheless, the intricate mechanisms underlying MLT/MT2’s protective role in DRG neurons in chemotherapy-induced neuropathic pain require further elucidation.…”
Section: Introductionmentioning
confidence: 99%